Measuring APC/C dependent ubiquitylation in vitro - Jarvis, Marc A. (Methods Mol Biol, 2016)
The anaphase promoting complex/cyclosome (APC/C) is a 1.2 MDa ubiquitin ligase complex with important functions in both proliferating and post-mitotic differentiated cells. In proliferating cells, APC/C controls cell cycle progression by targeting inhibitors of chromosome segregation and mitotic exit for degradation by the 26S proteasome. To understand how APC/C recruits and ubiquitylates its substrate proteins and how these processes are controlled, it is essential to analyse APC/C activity in vitro. In the past, such experiments have been limited by the fact that large quantities of purified APC/C were difficult to obtain and that mutated versions of the APC/C could not be easily generated. In this chapter we review recent advances in generating and purifying recombinant forms of the human APC/C and its co-activators, using methods that are scalable and compatible with mutagenesis. We also describe a method that allows the quantitative analysis of APC/C activity using fluorescently labelled substrate proteins.